2011
DOI: 10.3201/eid1707.101509
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Control of Legionellosis, Singapore

Abstract: To determine trends and clinical and epidemiologic features of legionellosis in Singapore, we studied cases reported during 2000–2009. During this period, 238 indigenous and 33 imported cases of legionellosis were reported. Cases were reported individually and sporadically throughout each year. Although the annual incidence of indigenous cases had decreased from 0.46 cases per 100,000 population in 2003 to 0.16 cases per 100,000 in 2009, the proportion of imported cases increased correspondingly from 6.2% duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 24 publications
3
14
1
3
Order By: Relevance
“…These symptoms have been reported previously as a common clinical signs of legionellosis caused by L. pneumophila [27]. Chon Lam et al (2011) [24] reported that the main clinical features of reported cases of RTIs caused by L. pneumophila were cough (77.9%), fever (72.7%), shortness of breath (32.5%), chest pain (13.3%) and nausea (11.8%) which was similar to our results.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These symptoms have been reported previously as a common clinical signs of legionellosis caused by L. pneumophila [27]. Chon Lam et al (2011) [24] reported that the main clinical features of reported cases of RTIs caused by L. pneumophila were cough (77.9%), fever (72.7%), shortness of breath (32.5%), chest pain (13.3%) and nausea (11.8%) which was similar to our results.…”
Section: Resultssupporting
confidence: 92%
“…A total of 202 patients hospitalized with a diagnosis of CAP were enrolled in a Korean study and 3 samples (2.4%) were positive for L. pneumophila which also was lower than our results [23]. Total incidence of L. pneumophila in Southeast Asia was 0.28 cases per 100,000 population (0.1%) [24], while its incidence among European countries were 1.18% (100,000 cases in 2008) [25]. The above investigations highlight large differences in the prevalence of L. pneumophila.…”
Section: Resultscontrasting
confidence: 74%
“…La legionelosis (Enfermedad del legionario y Fiebre de Pontiac) es una infección respiratoria aguda vinculada al medio ambiente. Su origen es la bacteria Legionella, de la que en la actualidad se han descrito 52 especies y 70 serogrupos, 25 conocidas como causantes de enfermedad [1]. Fundamentalmente es Legionella pneumophila la responsable de la mayoría de las infecciones humanas, con serogrupo 1 como el principal.…”
Section: Introductionunclassified
“…is ubiquitous in the aquatic environment, particularly in warm (25–42°C) stagnant water (Kool et al ). Over 50 species and 70 serotypes have been identified (Lam et al , Yarom et al ), with Legionella pneumophila serotype 1 as the strain with the greatest public health significance in North America (http://www.cdc.gov/vitalsigns/legionnaires/). Since 2001, reported outbreaks of legionellosis in the US have increased 400%, and it has become the most commonly reported waterborne pathogen—responsible for two‐thirds of all drinking water outbreaks (http://www.cdc.gov/vitalsigns/legionnaires/).…”
mentioning
confidence: 99%